Information Acquisition, Uncertainty Reduction, and Pre-Announcement Premium in China - Guo, Rui; Jia, Dun; Sun, Xi (Review of Finance, 2023)
We examine the stock market returns in an environment in which the dates of the central bank’s information supply through public announcements are not prescheduled. We document that positive excess returns are accumulated as early as 3 days before China’s central bank releases the monthly data of monetary aggregates, which may be announced either early or late in a month. In particular, this pre-announcement premium exists only when an announcement arrives late in an announcement cycle. We provide a theoretical framework in which the degree of information acquisition in the market increases as the date approaches the end of an announcement cycle while investors are still waiting for the arrival of an announcement, a hypothesis that receives strong empirical support. We show that the information acquisition channel highlighted in Ai, Bansal, and Han (2022) explains the uncertainty reduction and the positive risk premium before monetary announcements in China.